AB0001 Association of dickkopf1–1 polymorphisms with radiological damage and periodontal disease in patients with early rheumatoid arthritis. (12th June 2018) - Cardona-Rincón, A.D.; Acevedo-Godoy, M.; Perdomo-Lara, S.; Chila, L.; Chalem Ch, P.; Bautista-Molano, W.; Valle-Oñate, R.; Bello-Gualtero, J.M.; Romero-Sanchez, C.
Abstract : Background: Rheumatoid arthritis (RA) is an autoimmune disease that primarily affects the joints but also has extra-articular manifestations such as Periodontal Disease (PD). The Dickkopf-1 (DKK-1) may have an active role in the regulation of bone biology and patients with RA that carry genetic variants of DKK-1 have greater bone damage Objectives: To investigate the polymorphisms of DKK-1 in patients with early RA (eRA) and its association with some rheumatic, radiological and periodontal variables. Methods: A cross-sectional study in 63 patients with eRA according to the ACR/EULAR 2010 criteria and PD based on the AAP/CDC and Prevention criteria. Serum markers rheumatoid factor (RF), erythrocyte sedimentation rate (ESR), C reactive protein (CRP) and anticitrullinated peptide antibodies (APCAs) were evaluated. Patients selected were over 18 and less than 65 years old and were on treatment with conventional disease modifying antirheumatic drugs. Rheumatic activity was assessed by scales disease activity score 28 and simplified disease activity index. Radiographs of hands and feet were evaluated using the Sharp-van der Heijde (SvH) and Simple Erosion Narrowing Scores (SENS). DKK-1 polymorphisms as rs1896368, rs1896367 and rs1528873 were determined using the High resolution Melting technique (Bio-Rad). A bivariate analysis was performed to determine the variables associated between polymorphism to the presence of radiological and activity scores, diagnosis and severity of PD. A regression model was performed to confirm these associations. Results: The mean age was 48.57±11.35 years, and 76.7% were female. 11.7% had a body mass index >30 kg/m2. 35% had an ESR >20 mm/h, and 56, 7% had elevated CRP. RF >20 was observed in 61, 7% of patients as were ACPAs>20 in 43, 3% of them. 30%, 42% and 1.6% of patients were homozygous for polymorphism rs1896367, rs1896368 and rs1528873 respectively. Individuals heterozygous for polymorphism rs1896367 had more frequent erosions (p=0.026) and joint space narrowing (JSN) (p=0.005) in the feet, and consequently higher SHS scores (p=0.016). These patients also had higher SENS scores (p=0.001) and more frequent erosions (p=0.02). In contrast, patients homozygous for polymorphism rs 1896368 had less frequent JSN in hands and feet as assessed by SHS, as well as less presence of erosions based on the SENS scale. These findings were validated in the regression model (OR: 0.04, 95% CI:0.00–0.93;p<0.05). Finally, the presence of PD was associated with the homozygous expression of polymorphism rs 1896367 (p=0.009) and the heterozygous expression of polymorphism rs1696368 (p=0.033). Conclusions: DKK-1 polymorphisms can be associated with the presence of bone damage in patients with eRA and it could affect periodontal outcomes. While polymorphism rs1696367 seems to be associated with greater radiological compromise, polymorphism rs1696368 confers protection against bone damage in Colombian eRA patients. Reference: [1] De Rooy D, et al. Ann Rheum Dis. 2013;72:769–75. Disclosure of Interest: None declared